Extracellular Neuroleukin Enhances Neuroleukin Secretion From Astrocytes and Promotes Axonal Growth in vitro and in vivo - Tanie, Yoshitaka; Tanabe, Norio; Kuboyama, Tomoharu; Tohda, Chihiro (Frontiers in Pharmacology, 2018)
Under pathological conditions in the central nervous system (CNS), including spinal cord injury, astrocytes show detrimental effects against neurons. It is also known that astrocytes sometimes exert beneficial effects, such as neuroprotection and secretion of axonal growth factors. If beneficial effects of astrocytes after injury could be induced, dysfunction of the injured CNS may improve. However, a way of promoting beneficial functions in astrocytes has not been elucidated. In the current study, we focused on neuroleukin (NLK), which is known to have axonal growth activities in neurons. Although NLK is secreted from astrocytes, the function of NLK in astrocytes is poorly understood. We aimed to clarify the mechanism of NLK secretion in astrocytes and the functional significance of secreted NLK from astrocytes. Stimulation of cultured astrocytes with recombinant NLK significantly elevated the secretion of NLK from astrocytes. Furthermore, astrocyte conditioned medium treated with NLK increased axonal density in cultured cortical neurons. Recombinant NLK itself directly increased axonal density in cultured neurons. These results indicated that NLK secreted from astrocytes acted as an axonal growth factor and that secretion was stimulated by extracellular NLK. To elucidate a direct binding molecule of NLK on astrocytes, drug affinity responsive target stability (DARTS) analysis was performed. A 78 kDa glucose regulated protein (GRP78) was identified as a receptor for NLK, which was related to the secretion of NLK from astrocytes. When NLK was injected into the lesion site of spinal cord injured mice, axonal density in the injured region was significantly increased and hindlimb motor function improved. These results suggested that NLK-GRP78 signalling was important for the beneficial effects of astrocytes. This study strengthens the potential of astrocytes for use as therapeutic targets in CNS traumatic injury.